A Decision-Making Tool for Planning O&M Activities of Offshore Wind Farms Using Simulated Actual Decision Drivers - Tomaselli, Pietro D.; Dixen, Martin; Bolaños Sanchez, Rodolfo; Sørensen, Jacob Tornfeldt (Frontiers in Marine Science, 2021)
Safe and cost-efficient planning Operation&Maintenance (O&M) activities for the turbines of Offshore Wind Farms is crucial for the offshore wind industry. The execution of the planned tasks depends on the workability at sea. Workability assessments aim to find time periods, called weather windows, during which the personnel can execute the job at hand safely. Traditionally, weather windows analyses are based on thresholds applied on relevant metocean conditions in the area of interest, commonly wave height, wave period and wind speed. In this way, tasks are planned in windows during which the forecast metocean conditions do not exceed the defined thresholds. This paper presents a numerical tool that provides weather windows based on more direct measures of workability, that is seasickness on board during the trip to the turbines and bow motions, which endanger crew transfers from vessel to turbine. When assessing weather windows, such parameters better describe the actual decision drivers in a real operational setting than mere metocean thresholds, which are, in practical cases, discretionally judged by the O&M operator upon experience. Therefore, the reliability of workability predictions can increase, leading to financial gains for the wind industry and safer environment for O&M operators. The paper shows an application of the tool, where a full O&M scenario is simulated. The scenario comprises the transit from the port to the offshore site, the work carried out on the turbine and the transit back to the port. In particular, the application highlights the key capability of the tool of calculating vessel motions, which are elaborated to produce weather windows. With its low computational time-demand, the tool aims to support the decision-making processes that produce short- and long-term O&M plans.